Nuclear Stopping in Central Au+Au Collisions at RHIC Energies - Ying Yuan; Nana Guan (Advances in High Energy Physics)
Nuclear stopping in central Au+Au collisions at relativistic heavy-ion collider (RHIC) energies is studied in the framework of a cascade mode and the modified ultrarelativistic quantum molecular dynamics (UrQMD) transport model. In the modified mode, the mean field potentials of both formed and “preformed” hadrons (from string fragmentation) are considered. It is found that the nuclear stopping is increasingly influenced by the mean-field potentials in the projectile and target regions with the increase of the reaction energy. In the central region, the calculations of the cascade model considering the modifying factor can describe the experimental data of the PHOBOS collaboration.